1988
DOI: 10.1111/j.1751-1097.1988.tb02888.x
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation Dynamics of Local Anesthetics in Hydrophobic Media: Dibucainehci in Water/Alcohol or Surfactant Mixtures

Abstract: Abstract— The emitting chromophores, emitting states, state orderings and phosphorescence lifetimes of neutral, hydrogen‐bonded, and protonated dibucaines in water/alcohol mixtures were determined experimentally and were confirmed theoretically using a HAM/3 method. These photophysical properties are used to probe the deprotonation dynamics of dibucaine‐HCl in the water/hydrophobic media. It is found that the protonated dibucaine in an aqueous solution is deprotonated and/or forms hydrogen‐bonded dibucaine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The results revealed that the photophysical properties of free base, hydrogen-bonded and protonated dibucaines are quite unique and distinguishable from one another. These properties were used to probe the deprotonation of dibucaine.HC1 in the waterihydrophobic media (Lin et al, 1988). The second aspect is the characterization of the action sites and action mechanisms by the incorporation of drug species in the membrane.…”
Section: Tatracaine Proaimmentioning
confidence: 99%
“…The results revealed that the photophysical properties of free base, hydrogen-bonded and protonated dibucaines are quite unique and distinguishable from one another. These properties were used to probe the deprotonation of dibucaine.HC1 in the waterihydrophobic media (Lin et al, 1988). The second aspect is the characterization of the action sites and action mechanisms by the incorporation of drug species in the membrane.…”
Section: Tatracaine Proaimmentioning
confidence: 99%
“…Deprotonation of dibucaine occurred when the amine was brought in contact with lipophilic environments (Lin et al 1988). Based on the commonly used interpretation of 9-AA fluorescence signals (Schuldiner et al 1972), further evidence against 'classical' amine-type uncoupling by dibucaine comes from the observation that ApH inhibition was not dependent on the strength of ApH (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 -6 The experimental set-up for recording the fluorescence and phosphorescence spectra and lifetimes at 77 K has also been described elsewhere. 4 …”
Section: Methodsmentioning
confidence: 97%
“…3 . 4 These offer as viable 'direct' emission probes for studying the nature of their solubilizing microenvironment in sol-gel matrix.…”
Section: Introductionmentioning
confidence: 99%